The Dialectic Of Human Effort And Divine Decree - Moch. Mahdiyan Nasikhin; Ulin Nuha; M. Faisal Abda'u; Zuhaeroh Zuhaeroh; Rita Febiyanti; Wildan Syauqi J; Punjung Punjung; Alfiyah Prafitri Enda (CV. Generasi Insan Rafflesia, 2026)
This article discusses the relationship between human effort (ikhtiyar) and divine destiny based on the thoughts of Ibn ‘Athaillah al-Sakandari in his book Al-Hikam. This study employs a literature review method to clarify misconceptions regarding the concept of determinism, which often leads to a fatalistic attitude or excessive resignation without action. The findings indicate that a correct understanding requires a balance between God's will and human freedom. Effort is an obligation that must be maximized, while destiny is the realization of the Divine will that encompasses all aspects of life. The concept of tawakkul (trust in God) is not interpreted as passivity, but as surrendering the final outcome after exerting maximum effort. Misunderstanding this concept can lead to a loss of moral responsibility, a weakened work ethic, and neglect of the law of cause and effect. The integration of effort and trust in God is highly relevant in character building, mental health, and the implementation of holistic Islamic education, producing individuals who are productive, rational, and socially responsible.